Why strengthening the linkages between research and practice is important: learning from Young Lives - Crivello, G; Murray, H (Young Lives, 2012)
Over the last decade, there has been increasing debate around how to most effectively use research evidence to inform policy processes. A two-year study led by Young Lives set out to identify challenges and opportunities for translating research into policy and practice in the area of child poverty and child protection. On the basis of two case studies – one focusing on orphanhood and vulnerability in Ethiopia and the other on children’s work in Andhra Pradesh, India – the team developed a consultative approach involving a mixed group of stakeholders in each country. The groups identified several barriers to using research to improve policy and practice for children. These included lack of interaction between stakeholder groups, problems with who sets research agendas, lack of resources for supporting research uptake, and researchers’ lack of awareness of policy contexts. Part of strengthening the links between research, policy and practice is supporting the inclusion of children’s perspectives and participation in this process.